Silence, The Origin Of Evangelization A Discourse With Max Picard, Raimon Panikkar, And Aloysius Pieris - Yap Fu Lan (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2011)
Abstract: Max Picard argues that silence is the source of the word. The word that does not come from silence equals noise. A true word, or meaningful speech, springs from silence. Raimon Panikkar and Aloysius Pieris contend that silence is a characteristic of God. God’s Silence is spoken through the Word, expressed through the language of Body and Blood, the person of Jesus Christ. Christian evangelization is prophetic. It responds to human suffering, following the dynamism of Silence and Word, of life-death-resurrection. Christian evangelization is not merely about delivering the Word of God, but also about returning to its origin, the Silence of God. Keywords: silence, evangelization, Body-and-Blood language, prophetic, human suffering. Abstrak: Max Picard berargumen, keheningan adalah sumber ucapan. Ucapan yang tidak berasal dari keheningan hanyalah suara bising tanpa makna. Ucapan atau kata-kata sejati yang bermakna bersumber dalam keheningan. Raimon Panikkar dan Aloysius Pieris berpendapat, keheningan adalah karakter Allah. Keheningan ilahi diungkapkan melalui Sabda, melalui bahasa Tubuh dan Darah, yakni pribadi Yesus Kristus. Evangelisasi Kristiani sesungguhnya bersifat profetik. Evangelisasi Kristiani tanggap terhadap penderitaan umat manusia, mengikuti dinamika Keheningan dan Sabda Illahi, atau dinamika hidup-kematian-kebangkitan. Evangelisasi Kristiani bukan hanya hal mewartakan Sabda, melainkan juga hal kembali kepada sumbernya yang sejati, yakni Keheningan Allah. Kata-kata Kunci: keheningan, evangelisasi, ”bahasa Tubuh-dan-Darah,” profetis, penderitaan manusia.